ChemInform Abstract: One New Unusual Sesterterpenoid and Four New Sesquiterpene Dimers from Inula britannica. Issue 22 (15th May 2015) - Zhang, Xu‐Feng; Ren, Jie; Cheng, Xiang‐Rong; Jin, Hui‐Zi; Zhang, Wei‐Dong
Abstract: One new unusual dibritannilactone A (I) and four dibritannilactones C‐E (structure examples (II)) are isolated together with nine known compounds.